2020
DOI: 10.3390/ijms21124194
|View full text |Cite
|
Sign up to set email alerts
|

UV-Pre-Treated and Protein-Adsorbed Titanium Implants Exhibit Enhanced Osteoconductivity

Abstract: Titanium materials are essential treatment modalities in the medical field and serve as a tissue engineering scaffold and coating material for medical devices. Thus, there is a significant demand to improve the bioactivity of titanium for therapeutic and experimental purposes. We showed that ultraviolet light (UV)-pre-treatment changed the protein-adsorption ability and subsequent osteoconductivity of titanium. Fibronectin (FN) adsorption on UV-treated titanium was 20% and 30% greater after 1-min and 1-h incub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 43 publications
0
25
0
Order By: Relevance
“…Therefore, UVC light is likely an efficient method of photofunctionalization [ 12 , 15 , 20 , 24 , 36 ]. Moreover, neither UVA nor UVC light irradiation cause topographic or morphologic changes on Ti implant surfaces [ 10 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, UVC light is likely an efficient method of photofunctionalization [ 12 , 15 , 20 , 24 , 36 ]. Moreover, neither UVA nor UVC light irradiation cause topographic or morphologic changes on Ti implant surfaces [ 10 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous in vitro and in vivo studies employed custom-photofunctionalized disks and cylinders [ 10 , 11 , 15 , 40 ]. Notwithstanding, little research has been conducted to determine the effects of UVC photofunctionalization on commercially available Ti dental implants, specifically, to clarify the chemical modifications of Ti implants and the possible influences on the osseointegration process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, it was observed that the morphology of the adsorbed RBM cells on the Ti surfaces. Many studies [ 58 , 59 ] have confirmed the adsorption behavior of proteins and cells using QCM measurements, but there are few studies that confirm whether cells are adsorbed after confirming the adsorption behavior. Surface treated Ti showed significantly higher F-actin expression and more filamentous and foliate pseudopodia than untreated surfaces, where the plasma-treated Ti showed the highest concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Osteoblasts were obtained from femurs of 10-week-old male Sprague Dawley following the method described elsewhere [ 31 , 32 , 33 ]. Cells were seeded onto either BPO material or TBB materials placed in 12-well culture dishes at a density of 6 × 10 4 cells/cm 2 .…”
Section: Methodsmentioning
confidence: 99%